Ultraclean technology handbook - Ohmi, Tadahiro (Marcel Dekker, 1993)
Evaluating the effectiveness of conventional wet processes for cleaning silicon wafers in semiconductor production, this reference reveals concrete measures to improve ultrapure water quality reviewing the structure and physical characteristics of ultrapure water molecules. The volume is divided int.